The employee experience: how employees make meaning of employee engagement. Issue 5 (2nd November 2019) - Lemon, Laura L.
ABSTRACT: This study sought to understand the lived experiences of employees by taking a co-creational approach to examine how employees make meaning of employee engagement. Phenomenological interviews ( n = 32) revealed that engagement starts with dialogue supported by active listening. Formal internal communication emerged from the data as a contributor to meaning-making, but not to the extent the previous literature would suggest. Dialogic interactions carried more weight in constructing employee engagement. Thus, the findings demonstrate that the meaning of employee engagement is in fact a paradoxical balancing act between co-creational and functionalistic approaches, offering an alternative theoretical understanding of how employees make meaning of their engagement experiences.